Determinan Perilaku SADARI pada Wanita Pekerja Industri - Liya Arista; Mahmudah Dwi Insani (Faletehan Health Journal, 2024)
Breast cancer was a serious health problem in women throughout the world. Although much research had been conducted regarding breast self-exam (BSE) behavior, there was still little research on female industrial workers. Female industrial workers had great potential for exposure to carcinogenic substances, besides their busy working hours and activities potentially became obstacles in carrying out routine checks at home. The research aimed to identify the determinants of BSE behavior among female industrial workers in the Karawang area. The study used a cross-sectional approach on 112 female workers aged > 18 years and married. The sampling technique used purposive sampling. The research instrument was a questionnaire measuring the level of knowledge, attitudes and behavior of BSE. The results showed that the majority of respondents had a high level of knowledge (60.7%), sufficient attitude (61.6%), and moderate level of BSE behavior (46.4%). The most influencing determinants of BSE behavior were family history of cancer (OR=13.490), level of knowledge (OR=11.904), attitude (OR=7.873) and education (OR=0.217) respectively. Family history of cancer gave the most significant influence because women with a family history of breast cancer can obtain information easily from the family. Individual internal factors such as knowledge and attitudes also influenced BSE behavior. Therefore, an active role from health workers and workers in industrial work areas was needed to raise awareness about breast cancer and the need for regular BSE.